10. Jahresbericht des Instituts für Organisationsökonomik; Tenth annual report of the Institute for Organisational Economics - Alexander Dilger; Lars Vischer (Institut für Organisationsökonomik, 2020)
Das Institut für Organisationsökonomik (IO) an der Westfälischen Wilhelms-Universität Münster wurde am 1. Oktober 2020 zehn Jahre alt. Dieser 10. Jahresbericht informiert über das zehnte Jahr, d. h. über das Wintersemester 2019/20 und das Sommersemester 2020. Wie in den Vorjahren werden das Institut und seine Angehörigen vorgestellt. Danach wird über die Forschung und Lehre sowie weitere Aktivitäten des Instituts berichtet. – – The Institute for Organisational Economics at the University of Münster became ten years old on October 1st, 2020. This tenth annual report informs about the tenth year, the winter semester 2019/20 and the summer semester 2020. As in the previous years, the institute and its members are presented, followed by reports on research, teaching and further activities of the institute.
Keywords: 650